Covid-19’s influence on Africa’s university governance domain: debriefing South Africa–Nigeria settings - Okudolo, Ikemefuna Taire Paul; Amenaghawon, Francis (Penerbit Universiti Kebangsaan Malaysia, 2022)
Studies acknowledge that COVID-19 is a game-changer resulting in an operational “new normal” across organizational endeavours including university governance. One effect of COVID-19 on social change organizations like universities in Africa is that it intensified operational disruptions. The study utilizes narrative analysis to evaluate the impact of COVID-19 on university governance using South Africa-Nigeria settings as a template to generalize for Africa. Its data stems from a methodological qualitative orientation, implying that the narrations derive from unstructured interviews with key players within the university system. It is anchored on a conceptual framework founded on the ontology of African administrative and organizational culture that dialectically prompts epistemological analysis. The ontology facet deals with the status quo of university governance before COVID-19, denoting universities as mini societies reflecting the continent’s general operational culture. The epistemology aspect dealt with knowledge generation, indicating innovation African universities need to adopt to operate effectually during and aftermath of COVID-19. It finds that e-university governance application in Nigeria is underdeveloped compared to South Africa’s model which is basic. However, it concludes that improved investment in digitalizing operations of universities is imperative for their successful governance in a post COVID-19 pandemic epoch in Africa.